Ruling Out the Rule of Law - Forde-Mazrui, Kim (2007)
Although criminal justice scholars continue to debate the overall value of the void-for-vagueness doctrine, broad consensus prevails that requiring crimes to be defined in specific terms reduces law enforcement discretion. A few scholars have questioned this assumption, but the conventional view remains dominant. This Article intends to resolve the question whether the void-for-vagueness doctrine really reduces police discretion. It focuses on traffic enforcement, a context in which laws are both specific and subject to discretionary enforcement. The Article concludes that specific rules do not constrain discretion unless judicial limits are placed either on the scope of activities that may be criminalized or on police authority to under- enforce the laws. The Article also argues that the Supreme Court's response to specific-rule discretion is inadequate. The Court reassures us that the Equal Protection Clause protects against discriminatory traffic enforcement. However, the Court fails to appreciate that antidiscrimination review is inherently ineffective when applied to broadly discretionary decisions. Legislatures have thus circumvented existing doctrinal constraints on delegating discretion, but the Court has failed to develop an adequate doctrinal response. Finally, the Article considers some remedial and constitutional implications of its analysis. Ultimately, the Article argues, judicial checks on specific-rule enforcement are required to maintain a balance between individual liberty and crime control in a constitutional regime committed to the rule of law